Survey-based evaluation of the awareness of pharmaceutical specialists on the pharmacotherapy of climacteric syndrome - M. A. Chernyavskaya; I. A. Narkevich (Фармакоэкономика)
Objective: to evaluate the awareness of pharmaceutical specialists on the pharmacotherapy of climacteric syndrome based on survey results.Material and methods. The authors analyzed 394 surveys of pharmaceutical specialists in Saint-Petersburg. The survey consisted of 13 questions, covered the personal characteristics of the participants (age, education, professional experience) and their knowledge about special medicines and food supplements to control climacteric symptoms, indications, and contraindications.Results. The results showed that pharmaceutical specialists saw the difference between combined oral contraceptives and menopausal hormone therapy, but they do not know about the protective cardiovascular effects of menopausal hormone therapy. Most specialists consider menopausal hormone therapy more effective than phytoestrogens, but they have no idea how it works. For most of them, there is hardly any difference between various classes of phytoestrogens. In their opinion, medical representatives and scientific conferences are the main providers of medical information.Conclusion. The analysis of the level of awareness of pharmaceutical specialists about the pharmacotherapy of menopausal syndrome based on the results of the survey revealed insufficient knowledge among pharmacy workers on a number of fundamental issues. Therefore, it is necessary to develop methodological recommendations on menopausal hormone therapy preparations and phytoestrogens-based drugs for pharmaceutical specialists who act as an important intermediate between a doctor and a patient.